Juozas Narūnavičius–Naronskis, a mathematician and cartographer (1610–1678) - Gečiauskas, Evaldas (Lietuvos matematikos rinkinys, 2004)
Juozas Narūnavičius-Naronskis was Eques Lituanus. He distinguished himself by cartographing the estates of Jonušas Radvila and he has drawn a map of Biržai principality. In 1659, he wrote the works Arithmetica, Geometria, and Architectura militaris. The same year, due to the persecution of antitrinitians he left for East Prussia under the guardianship of Boguslavas Radvila who become thė governor for East Prussia nominatedby Brandenburg elector Friedrich Wilhelm in 1657. On the instructions of the elector J. Naronskis drew maps of 44 local districts in East Prussia. In 1665 he wrote his work Artileria, and in 1669 – Complement to his book Arithmetica. He wrote his works in the Polish language so that the neighbouring slavonic peoples could understand them.